Allometric equations for predicting aboveground biomass of beech-hornbeam standsin the Hyrcanian forests of Iran - A.A. Vahedi; A. Mataji; S. Babayi-Kafaki; J. Eshaghi-Rad; S.M. Hodjati; A. Djomo (Journal of Forest Science, 2014)
A better understanding of the carbon biomass from forests is needed to improve both models and mitigation efforts related to the global C cycle and greenhouse gas mitigation. Despite the importance of Hyrcanian forests for biodiversity conservation, no study with biomass destruction has been done to predict biomass and carbon pools from this forest. Mixed-specific regression equations with 45 sample trees using different input variables such as diameter, height and wood density were developed to estimate the aboveground biomass of beech-hornbeam stands. All the sample trees were harvested and the diameter at breast height (DBH) spanned from 31 to 104 cm so as to represent the diameter distribution reported in the beech-hornbeam stand management. Using only diameter as an input variable, the stands regression model estimates the aboveground biomass of the stand with an average deviation of 19% (R2adj = 0.92; SEE = 0.22). Adding height as the second explanatory variable slightly improved the estimation with an average deviation of 18% (R2adj = 0.95; SEE = 0.17). Adding only height or wood density did not improve significantly the estimations. Using the three variables together improved the precision of bole biomass prediction of stands with an average deviation of 10.3% (R2adj = 0.965; SEE = 0.167). 68% of the observed variation in the aboveground biomass of beech-hornbeam stands was explained only by diameter.